2023
DOI: 10.1093/noajnl/vdad048
|View full text |Cite
|
Sign up to set email alerts
|

UBE2C promotes leptomeningeal dissemination and is a therapeutic target in brain metastatic disease

Abstract: Background Despite current improvements in systemic cancer treatment, brain metastases (BM) remain incurable, and there is an unmet clinical need for effective targeted therapies. Methods Here, we sought common molecular events in brain metastatic disease. RNA sequencing of thirty human BM identified the upregulation of UBE2C, a gene that ensures the correct transition from metaphase to anaphase, across different primary tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…These studies were chosen based on information on chemotherapeutic resistance, signaling pathways, and mechanisms that shed light onto possible therapeutic strategies. [ [75][76][77][78] Abbreviations. UBE2C: ubiquitin-conjugating enzyme, HER2: human epidermal growth factor receptor 2, p53: tumor suppressor p53, Ki67: marker of proliferation Ki-67, PI3K: phosphoinositide 3-kinase, EGFR: epidermal growth factor receptor, HIF-1α: hypoxia-inducible factor 1-alpha, NSCLC: non-small cell lung carcinomas, TNM: TNM Classification of Malignant Tumors, AKT: AKT serine/threonine kinase, CTLA4: cytotoxic T-lymphocyteassociated protein 4, EMT: epithelial-mesenchymal transition, TFH: T follicular helper cells, FoxM1: Forkhead box M1, AURKB: aurora kinase B, mTOR: mammalian target of rapamycin.…”
Section: Ube2c and Systemic Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…These studies were chosen based on information on chemotherapeutic resistance, signaling pathways, and mechanisms that shed light onto possible therapeutic strategies. [ [75][76][77][78] Abbreviations. UBE2C: ubiquitin-conjugating enzyme, HER2: human epidermal growth factor receptor 2, p53: tumor suppressor p53, Ki67: marker of proliferation Ki-67, PI3K: phosphoinositide 3-kinase, EGFR: epidermal growth factor receptor, HIF-1α: hypoxia-inducible factor 1-alpha, NSCLC: non-small cell lung carcinomas, TNM: TNM Classification of Malignant Tumors, AKT: AKT serine/threonine kinase, CTLA4: cytotoxic T-lymphocyteassociated protein 4, EMT: epithelial-mesenchymal transition, TFH: T follicular helper cells, FoxM1: Forkhead box M1, AURKB: aurora kinase B, mTOR: mammalian target of rapamycin.…”
Section: Ube2c and Systemic Cancermentioning
confidence: 99%
“…Recently, Paisana et al reported the association of UBE2C and BM [78]. The authors have demonstrated that UBE2C is highly expressed in human BM from different primary tumors in comparison to normal tissues.…”
Section: Ube2c and Brain Cancer Invasion And Disseminationmentioning
confidence: 99%
See 2 more Smart Citations